2020
DOI: 10.1098/rsbl.2020.0238
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine increases individual and collective foraging in a neotropical stingless bee

Abstract: The biogenic amine octopamine (OA) is a key modulator of individual and social behaviours in honeybees, but its role in the other group of highly eusocial bees, the stingless bees, remains largely unknown. In honeybees, OA mediates reward perception and affects a wide range of reward-seeking behaviours. Thus, we tested the hypothesis that OA increases individual foraging effort and collective food source exploitation in the neotropical stingless bee Plebeia droryana . OA treatment cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Our understanding of how OA mediates collective foraging in other social bees (e.g. Meliponinae; Mc Cabe et al, 2017; Peng et al, 2020) is equally limited. Within Bombus , only five prior studies have, to our knowledge, directly measured or manipulated OA.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of how OA mediates collective foraging in other social bees (e.g. Meliponinae; Mc Cabe et al, 2017; Peng et al, 2020) is equally limited. Within Bombus , only five prior studies have, to our knowledge, directly measured or manipulated OA.…”
Section: Discussionmentioning
confidence: 99%
“…Social insect behaviour and, in particular, foraging strategies are linked to gene expression in the brain (Ingram et al, 2011; Robinson et al, 2008; Toth & Robinson, 2009; Toth et al, 2010; Zayed & Robinson, 2012). Behavioural variation among workers and within foragers seems to be strongly connected to biogenic amine signalling, such as dopamine, octopamine, tyramine, and serotonin signalling (Arenas et al, 2020; Barron et al, 2002; Liang et al, 2012; Linn et al, 2020; Mercer & Menzel, 1982; Peng et al, 2020, 2021; Scheiner et al, 2002, 2017; Schulz et al, 2003). Transcriptomic differences between behavioural groups were typically studied by investigating the entire brain (e.g., Alleman et al, 2019; Liang et al, 2012; Whitfield et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In M. scutellaris octopamine increases gustatory responsiveness similar to honeybees [McCabe et al, 2017]. In another stingless bee, Plebeia droryana, octopamine treatment increases the number of bees at artificial sucrose feeders, which was interpreted by an octopaminedriven lowering of the individual sucrose response threshold [Peng et al, 2020], similar to the effect observed in honeybees [Barron et al, 2002;Barron and Robinson, 2005]. However, these data suggest that modulation of sucrose responsiveness is likely more complex and, in addition to tyramine and its specific receptors, further modulators such as octopamine have to be considered.…”
Section: Discussionmentioning
confidence: 91%